The Influence Of Motivation And Work Discipline On Employee Performance Pt Fatona Unit Of Pt Yumeida Utama Medan - Tinambunan, Eka Santa Darmawati; Hasibuan, Hasrul Azwar; Alfahmi, Muhammad (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Understanding the impact of work discipline (X2) and motivation (X1) on employee performance (Y) at PT. Yumeida Utama Unit PT. Fatona Medan is the aim of this study. Forty-five employees of PT. Yumeida Utama Unit PT. Fatona comprised the study's population. The population, or 45 respondents, is the number of samples collected. In 2025, the investigation was carried out. In this work, Using SPSS version 22, to assess quantitative data, a multiple linear regression model was employed. The study's findings showed that employee performance can be improved through work motivation. Motivation and encouragement of staff are the main priorities of the PT. Fatona unit PT. Yumeida Utama in order to produce satisfactory staff performance. Workplace employee performance is significantly impacted by punishment. This shows how the PT. Fatona unit at PT. Yumeida Utama applies strong discipline to create positive working conditions, which can develop staff performance. The F count (36.335) > F table (3.22) and the F test value Sig. (0.000) <0.05. This implies that employee performance is significantly affected by work discipline and motivation.